Verbal Training Induces Enhanced Functional Connectivity in Japanese Healthy Elderly Population - Yang, Fan-Pei Gloria; Liu, Tzu-Yu; Liu, Chih-Hsuan; Murakami, Shumei; Nakai, Toshiharu (Frontiers in Human Neuroscience, 2022)
This study employs fMRI to examine the neural substrates of response to cognitive training in healthy old adults. Twenty Japanese healthy elders participated in a 4-week program and practiced a verbal articulation task on a daily basis. Functional connectivity analysis revealed that in comparison to age- and education-matched controls, elders who received the cognitive training demonstrated increased connectivity in the frontotemporal regions related with language and memory functions and showed significant correlations between the behavioral change in a linguistic task and connectivity in regions for goal-oriented persistence and lexical processing. The increased hippocampal connectivity was consistent with previous research showing efficacious memory improvement and change in hippocampal functioning. Moreover, the increased intra-network connectivity following cognitive training suggested an improved neural differentiation, in contrast to the inter-network activation pattern typical in the aging brain. This research not only validates the relationship of functional change in the frontal and temporal lobes to age-associated cognitive decline but also shows promise in turning neural change toward the right direction by cognitive training.